Cytomegalovirus infection alters phenotypes of different ?d T-cell subsets in renal transplant recipients with long-term stable graft function - Lee, S.; Affandi, Jacquita; Irish, A.; Price, P. (WILEY-LISS, 2017)
© 2017 Wiley Periodicals, Inc. Cytomegalovirus (CMV) infection alters the phenotypic profiles of T-cells and NK cells in healthy and immunocompromised individuals. Here, we examined the effects of CMV infection on the phenotype and functions of ?d T-cell subsets in renal transplant recipients (RTR) stable several years after transplantation (n = 80) and healthy controls (n = 72). Differentiation status, function, and expression of HLA-DR, CD57, and LIR-1 on Vd2 - and Vd2 + ?d T-cells were examined in peripheral blood cells using flow cytometry. Percentages of Vd2 - ?d T-cells were higher in RTR who are CMV-seropositive and correlated with CMV antibody levels. Proportions of Vd2 - ?d T-cells expressing HLA-DR, CD57, or LIR-1 were increased in CMV-seropositive RTR and healthy controls compared to their seronegative counterparts. Additionally, Vd2 - ?d T-cells were skewed towards a terminally differentiated phenotype and most expressed CD8 in individuals who were CMV-seropositive. Increased expression of LIR-1 on terminally differentiated Vd2 - ?d T-cells was associated with CMV seropositivity in RTR and controls. The presence of CMV DNA in 15 RTR was associated with higher frequencies of LIR-1+ Vd2 + ?d T-cells and increased percentages of terminally differentiated effector memory cells in both ?d T-cell subsets. Our study further characterises the effects of CMV and transplantation on ?d T-cell phenotypes.